Redox-driven photoselective self-assembly - Dario Alessi; Luca Morgan; Elisa Pelorosso; Claudia Graiff; Piermaria Pinter; Alessandro Aliprandi (Nature Communications)
Abstract Self-assembly via non-covalent interactions is key to constructing complex architectures with advanced functionalities. A noncovalent synthetic chemistry approach, akin to organic chemistry, allows stepwise construction with enhanced control. Here, we explore this by coupling Pt(II) complex self-assembly with a redox reaction. Oxidation to Pt(IV) creates a non-emissive monomer that, upon reduction to Pt(II), forms luminescent gels with unique kinetic and thermodynamic pathways. UV irradiation induces Pt(IV) reduction, generating supramolecular fibers with Pt∙∙∙Pt interactions, enhancing photophysical properties and enabling visible light absorption up to 550 nm. This allows photoselective growth, where fibers convert surrounding Pt(IV) to Pt(II), promoting growth over nucleation, as observed via real-time fluorescence microscopy.